Enhancing Energy Security through Utilization of Local Resources: Case Study: Biomass/Biogas Utilization in Berau Regency, East Kalimantan - Adiwibowo, Indradarma; Lestari, Dita Anggun; Manalu, Davit (Indonesian Journal of Energy, 2018)
Remote rural villages in Indonesia do not have sufficient infrastructure to maintain an economically sound energy generation and distribution. Sparse area and low population hinder national electricity company PLN (Perusahaan Listrik Negara) to connect these remote rural villages to the national grid. Most of the villages lie in the palm oil plantation, where renewable biomass resources from the Palm Oil Mill wastes are plentiful. Untapped biomass resources could be the answer to energy security issue in the remote rural area. Berau Regency in East Kalimantan Province has many villages located in the palm oil plantation area. Nearly all of the palm oil processing plants in Berau use palm shell and fiber to power the mill. Some of them have the agreement with PLN to sell their excess power. This scheme can be applied to provide electricity to villages around the palm oil mills. However, it is unreliable since the amount of excess electricity produced keeps fluctuating. This paper explores the idea of village-owned biomass/biogas power plant that is owned and operated by the villagers themselves. That way, the village can ensure its energy security using sustainable local resources. In conclusion, the investment cost of biomass/biogas power plant cannot be provided by village annual budget. Although the villages in Berau Regency have a relatively high annual budget, wich is about Rp2 billion to Rp5 billion, the investment costs of biomass/biogas power plant is even higher. According to the economic analysis of biomass/biogas power plant development, a biomass power plant with 1,7 MW capacity can cost up to Rp46 billion. Moreover, a biogas power plant with 1 MW capacity costs around 41 billion. It is not possible for the villages to finance the power plant development by themselves. Therefore, the private sector is needed to implement biomass/biogas utilization for rural electrification from palm oil waste. With the Net Present Value (NPV) up to Rp 65.078.072.000,00 and Internal Rate of Return (IRR) of 20% for biomass power plant and Rp14.330.070.000,00 and 10% for biogas power plant, it is economically feasible and profitable for private enterprise to undertake. The challenges are for the government to encourage the private sector to invest and for PLN to sign Power Purchase Agreement with these palm oil enterprises rather than just Excess Power Agreement. JEL Classification: I39